The Sharp Bound of the Third Hankel Determinant for the Inverse of Bounded Turning Functions (Contemporary Mathematics, 2023)
The objective of this paper is to estimate the best possible upper bound to the third Hankel determinant for the inverse of functions with normalized conditions f (0) = 0, f ′(0) = 1 in the unit disc whose derivative has positive real part.
Keywords: Holomorphic function, Hankel determinant, inverse of bounded turning function, Carathéodory function